2017
DOI: 10.1177/1940082917709648
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Chinese Pangolin’s (Manis pentadactyla) Diet in a Peri-Urban Habitat

Abstract: Gut content analysis of a juvenile Chinese pangolin revealed eight ant and one termite species being preyed on. The identification of > 26,000 prey items and a comparison with local ant communities suggest a selective foraging behavior and a tendency for direct predation on arboreal or epigaeic ant nests within secondary forest and shrubland habitats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…On the first day of the feeding trials at 16:00, we provided 60 g of O. formosanus (18,816 individuals estimated by mass) or 15–20 g of A. gracilipes (14,400–19,200 individuals estimated by mass) mixed thoroughly with artificial food and 0.25 g of Cr 2 O 3 (a maker that produces green feces) to form a 100 g diet for each pangolin. The number of termites or ants used in this study is similar to that found in the gut of a wild Chinese pangolin reported by Lee et al (2017). Although the body length of termites and ants are quite similar (Figure 1a,b), termites contain more water than do ants (Redford & Dorea, 1984).…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…On the first day of the feeding trials at 16:00, we provided 60 g of O. formosanus (18,816 individuals estimated by mass) or 15–20 g of A. gracilipes (14,400–19,200 individuals estimated by mass) mixed thoroughly with artificial food and 0.25 g of Cr 2 O 3 (a maker that produces green feces) to form a 100 g diet for each pangolin. The number of termites or ants used in this study is similar to that found in the gut of a wild Chinese pangolin reported by Lee et al (2017). Although the body length of termites and ants are quite similar (Figure 1a,b), termites contain more water than do ants (Redford & Dorea, 1984).…”
Section: Methodssupporting
confidence: 85%
“…Several previous studies have reported proportions of termites in free‐ranging pangolin diets, although the results were not consistent. Lee et al (2017) dissected the gut of one Chinese pangolin and found that termites constituted only 3.1% of the insect individuals in the gut, and the rest were ants. In research on the Indian pangolin ( M. crassicaudata ), termite cuticles remaining in the feces constituted a small percentage of the gut content (Irshad et al, 2015) or were not recovered (Mahmood et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forest areas are reported to be a resource for termites and ants [66][67][68][69], common prey species of Chinese pangolins. We found a greater potential distribution of Chinese pangolins in forest lands.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in peri-urban landscapes of the global south show that peri-urban landscapes can be vital biodiversity conservation areas [33][34][35][36][37][38][39][40] giving us a chance to maintain and protect the numerous and unaccountable ES benefits biodiversity provides to mankind [27,41,42]. In the Philippines, the majority of the ES related studies include traditional rice-based systems and their watershed services [43][44][45], mangroves [46,47], and indigenous agriculture-based systems in ancestral land [48].…”
Section: Introductionmentioning
confidence: 99%